Entering the fray : gender, politics, and culture in the New South - Wells, Jonathan Daniel, 1969-; Phipps, Sheila R., 1948- (Southern women., 2010)
"Taken together, these nine essays contribute to the picture of women increasing their movement into political and economic life while all too often still maintaining their gendered place as determined by society. Their rich insights provide new ways to consider the meaning and role of gender in the post-Civil War South."--Jacket.